Relationships between body mass index with oral estradiol dose and serum estradiol concentration in transgender adults undergoing feminising hormone therapy. (May 2020) - Nolan, Brendan J.; Brownhill, Adam; Bretherton, Ingrid; Wong, Peggy; Fox, Susan; Locke, Peter; Russell, Nicholas; Grossmann, Mathis; Zajac, Jeffrey D.; Cheung, Ada S.
Aim: Feminising hormone therapy with estradiol is used to align an individual's physical characteristics with their gender identity. Given considerable variations in doses of estradiol therapy administered as gender-affirming hormone therapy (GAHT), we aimed to assess if body mass index (BMI) correlated with estradiol dose/concentration and assess the correlation between estradiol dose and estradiol concentrations. Methods: In a retrospective cross-sectional study, we analysed transgender individuals attending a primary or secondary care clinic in Melbourne, Australia who were prescribed oral estradiol valerate for at least 6 months and had estradiol dose and concentration available. Estradiol concentration was measured by immunoassay. Outcomes were the correlation between estradiol dose and BMI, and estradiol dose and estradiol concentration. Results: Data were available for 259 individuals median age 25.8 [interquartile range (IQR) 21.9, 33.5] years. Median duration of estradiol therapy was 24 (15, 33) months. Median estradiol concentration was 328 (238, 434) pmol/l [89 (65, 118) pg/ml] on 6 (4, 8) mg estradiol valerate. Median BMI was 24.7 (21.8, 28.6) kg/m 2 . There was a weak positive correlation between estradiol dose and estradiol concentration ( r = 0.156, p = 0.012). There was no correlation between BMI and estradiol concentration achieved ( r = −0.063, p = 0.413) or BMI and estradiol dose ( r = 0.048, p = 0.536). Estradiol concentrations were within the target range recommended in consensus guidelines in 172 (66%) individuals. Conclusion: Estradiol dose was only weakly correlated with estradiol concentration, suggesting significant interindividual variability. Prescription of estradiol dose should not be based upon an individual's BMI, which did not correlate with estradiol concentration achieved. In all, 66% of individuals achieved estradiol concentrations recommended in Australian consensus guidelines with a relatively high oral estradiol dose.